Sources, sinks, and cycling of dissolved organic copper binding ligands in the ocean - Angel Ruacho; Camille Richon; Hannah Whitby; Randelle M. Bundy (Communications Earth & Environment, 2022)
Margin sediments and rivers are the most significant sources of copper binding ligands in the ocean while sedimentation, microbial uptake and photochemical degradation are the major sinks, suggests a synthesis of research on the cycling of copper ligands in the oceans.